William's Social Psychology; Ogburn's Social Change - Dickinson, Z. C.; Williams, James Mickel; Ogburn, William Fielding (Quarterly Journal of Economics, 1923)
Journal Article Williams's Social Psychology; Ogburn's Social Change Get access Z. C. Dickinson Z. C. Dickinson University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 37, Issue 2, February 1923, Pages 369–373, https://doi.org/10.2307/1883936 Published: 01 February 1923